Substance as Reality in John Locke - Nazanin Zahra Bigdeli; ابراهیم موسوی; Hamed Shivapour (حکمت اسرا)
Lock’s doctrine of substance has a lot of difficulties. On the one hand, He considers substance as an unknown thing of which we just have a relative and ambiguous representation. On the other hand, He believes in corpuscularian hypothesis in which the physical world ultimately consists of atoms and physical corpuscles. The main question for Locke is what the place of substance is; is it real, or just subjective? Can substance be considered the very atoms and physical corpuscles? In other words, how these two views of Locke, i.e., the corpuscularian and unknowable hypotheses of substance, are compatible? To get the answer, first, we briefly explain Lock’s doctrine of substance, and then evaluate the article author's response to the issue. The author believes that the solution is the distinction between Locke's fields of intention to substance (the epistemological domain) and corpuscularian hypothesis (the ontological domain).